P‐19: Suppression of Light Induced Instability of BCE InGaZnO Transistors and Panel Flicker Improvement for 32‐in. 8K4K LCD. Issue 1 (May 2017) - Shi, Long-Qiang; Chen, Shu-Jhih; Chou, Yi-Fang; Ge, Shi-Min; Zhao, Yang; Zeng, Li-Mei; Zeng, Mian; Wang, Tian-Hong; Chen, Ren-Lu; Liao, Cong-Wei; Lv, Xiao-Wen; Li, Wen-Ying; et al.
Abstract : Illumination instability of BCE IGZO TFT was studied in this paper. It was found that the distance between island‐in IGZO and gate electrode is larger than 2μm (P2) could be able to resist light induced device deterioration effectively. We also found that P4 was an optimum distance for flicker performance compared to P2 design, the flicker level of P2 and P4 is 25dB and HdB respectively. Finally, a high performance 32‐inch 8K4K IGZO LCD was successfully demonstrated based on all the study above.